Current Log. Issue 2 (9th October 2020) - Atkinson, Claire
This editor's note gives an overview of the issue content and an update on the Current editorial board. It also calls for NMEA members to sign up as peer reviewers and submit articles that address NMEA's Strategic Plan Key Focus Areas.